2006
DOI: 10.1622/1059-8405(2006)22[330:tcaaio]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Cognitive and Academic Impact Of Sickle Cell Disease

Abstract: Sickle cell disease (SCD) affects over 30,000 students in the United States. Central nervous system complications are widespread among students with SCD and include stroke, silent cerebral infarction, and cognitive impairment. The effects of these complications may lead to academic failure, limited career options, and for some, total disability. Despite studies describing the significant academic and cognitive impact of sickle cell disease, reports describing interventions are limited. There is a lack of aware… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
1
10

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 0 publications
2
16
1
10
Order By: Relevance
“…The findings in this study were not in good agreement with the reports from previous studies that had observed statistically worse cognitive performance among children with SCA [11,33]. Day et al [8] observed from a review of studies comparing cognitive function among SCA patients and control that there was a significantly poorer performance in SCA patients in up to 71% of the papers reviewed. The findings of no significant difference in global cognitive performance between our SCA and controls despite the fact that there was statistically significant difference in the age of the SCA group and control is in good agreement with previous conclusion from a review.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…The findings in this study were not in good agreement with the reports from previous studies that had observed statistically worse cognitive performance among children with SCA [11,33]. Day et al [8] observed from a review of studies comparing cognitive function among SCA patients and control that there was a significantly poorer performance in SCA patients in up to 71% of the papers reviewed. The findings of no significant difference in global cognitive performance between our SCA and controls despite the fact that there was statistically significant difference in the age of the SCA group and control is in good agreement with previous conclusion from a review.…”
Section: Discussioncontrasting
confidence: 87%
“…The findings of no significant difference in global cognitive performance between our SCA and controls despite the fact that there was statistically significant difference in the age of the SCA group and control is in good agreement with previous conclusion from a review. Moreover, it observed that the age of controls among younger people has little effect on their performance [8].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Less oxygen, along with increased metabolic demands, may lead to delayed growth and sexual development, which can be very concerning to adolescents with SCD (Bennett, 2011;Sarjeant & Sarjeant, 2001). In addition, teens with SCD may have concerns regarding academic failure (Day & Chismark, 2006). SCD exacerbations and hospitalizations can negatively affect school attendance and attainment of educational goals.…”
mentioning
confidence: 99%